Lymphatic Malformation Architecture: Implications for Treatment With OK-432. Issue 7 (October 2017) - Malic, Claudia C.; Guilfoyle, Regan; Courtemanche, Rebecca J.M.; Arneja, Jugpal S.; Heran, Manraj K.S.; Courtemanche, Douglas J.
Abstract : Purpose: Herein, the authors aim to describe their findings of novel architectural types of lymphatic malformations (LM) and explain the relationship between these architectures and OK-432 treatment outcomes. Methods: A retrospective review was conducted of all patients diagnosed with a LM treated with OK-432 at the Vascular Anomalies Clinic at BC Children's Hospital from December 2002 to January 2012. Results: Twenty-seven patients were included in the study. Sixty percent of lesions were present by 2 years of age with the majority located in the head and neck (59%). The average number of sclerotherapy procedures was 1.4 per patient. Treatment under fluoroscopic guidance revealed 3 new LM architectures: open-cell microcystic, closed-cell microcystic, and lymphatic channel. Response to treatment was complete or good for 14/19 macrocystic and for 1/2 mixed lesions. Open-cell microcystic LMs gave a complete or good response for 3/3, which was attributed to OK-432 freely communicating between cysts. Closed-cell microcystic LM had localized cysts that did not allow OK-432 to freely communicate and were associated with partial responses, 2/2. The lymphatic channel had a partial response. There were 2 minor complications and 1 instance of recurrence. Conclusions: The identification of 3 new LM architectures expands the current accepted classification to include: open-cell microcystic, closed-cell microcystic, and lymphatic channels. The majority of complete responses to OK-432 were found with macrocystic lesions. Open-cell microcystic lesions respond better to OK-432 than closed-cell microcystic lesions, and lymphatic channels may respond to OK-432. These key architecture–response relationships have direct clinical implications for treatment with OK-432 sclerotherapy.